PENGARUH EFIKASI DIRI, SIKAP KEWIRAUSAHAAN, DAN POLA PIKIR KEWIRAUSAHAAN TERHADAP NIAT KEWIRAUSAHAAN - Nurningsih, Sari; Rosya, Nilma Desri; Saputri, Tiara Azhari; Risni, Serly Alima Giyan; Ihsan, Muhammad; reksabil, Kevin Aldea (STIE Perbankan Indonesia, 2024)
This research aims to analyze the influence of self-efficacy, entrepreneurial mindset and entrepreneurial knowledge on entrepreneurial intentions. This self-efficacy refers to an individual's belief in achieving desired goals, an entrepreneurial mindset, the need to explore business opportunities and entrepreneurial knowledge refers to business concepts and practices. This research is indicated as an effort to encourage entrepreneurial intentions among students to create competent young entrepreneurs using these three aspects. This type of research uses quantitative research with a sample of 133 respondents. The research results showed that self-efficacy, entrepreneurial attitude and entrepreneurial mindset had a positive effect on entrepreneurial intentions. Likewise, self-efficacy and mindset have a positive influence on entrepreneurial attitudes. Keywords: Self-Efficacy, Entrepreneurial Attitude, Entrepreneurial Mindset and Entrepreneurial Intentions.